Crime and punishment in Tercera Celestina by Gaspar Gómez de Toledo: a doctor's moralising view? - Folke Gernert (Celestinesca, 2021)
The present article studies the Tercera Celestina by Gaspar Gómez de Toledo as a work possibly written by a physician, placing particular emphasis on the textualisations of healing knowledge from a perspective of the history of science. A comparison with La Lozana Andaluza by the doctor Francisco Delicado shows parallels with the work of Gómez de Toledo who, like the Andalusian physician, makes moralistic judgements through the metaphor of illness and physical disability.